Multimedia Pembelajaran Interaktif tentang Pengenalan Bilangan untuk TK Dharmawangsa, Badung Bali - Sutarwiyasa, I Ketut; Anggara, I Gede Adi Sudi; Wirayoga, I Putu Ade; Wardana, Ketut Nala Hari; Herliyani, Elly; Suryana, Jajang (Prahasta Publisher (manage by: DRPM Institut Bisnis dan Teknologi Indonesia), 2024)
In the learning activities carried out at TK Dharmawangsa, students feel bored quickly during the learning process, especially when learning to recognize numbers. This is because the learning media used before were less attractive, because they only used books and makeshift tools. The design of interactive multimedia about number recognition is able to be a solution to this problem, because interactive multimedia is able to display text, graphics, audio, and animation to attract students' interest in the learning process. Therefore, the purpose of this study is to develop interactive learning multimedia that has a number recognition feature and contains games to arrange numbers and guess the number of objects to help students and teachers of TK Dharmawangsa in the teaching and learning process. For data collection techniques used in this study, namely observation, interviews, questionnaires, literature, and documentation. And for the method of making media starting from the pre-production process, production, to post-production. Based on the test results, the material experts get a very good predicate about this interactive media as an auxiliary media in the teaching and learning process, while the media experts get a good predicate about the appropriateness of this interactive media to be published. Based on the results of the questionnaire that was given to 21 students of TK Dharmawangsa, this interactive multimedia about number recognition received very good 100% responses as an interesting and fun learning medium.